Projeto inovador: uma alternativa para a formação do jovem na escola pública? - Sanches, Maria Cecilia (2009)
By means of a Case Study this research analyzed the Pedagogical Project of a public school located in the city of São Paulo considered innovative for its professionals and its community, with the purpose of checking what was its basis, what in fact was carried through and the way it was shown in the process of formation of the pupils, which were in the final levels of basic education. The collection of data was carried through between 2005 and 2008 by informal interviews, analysis of the school plan and other documents referring to the school, as well as the systematic comment of lessons and meetings. The analysis of the data was based on the workmanships of studious of Social Psychology, mainly in Henri Wallon (1968, 1973, 1975, 1979, 1986), focus on approaches related to intellectuals of the Sociology of the Education, with basis on authors who conceive the culture as the source to the constitution of the individual and the society: Canário (2005, 2006) and Pérez Gómez (1998, 2001). The results, which were obtained, confirmed the hypothesis that made reference to the relation to knowledge, the new role of the professor and the social function of the school that have been modified and clearly lost its reference with the traditional education and learning. The analysis had pointed out that loss and also shown the entrance of the community in the school, which occurred in detriment of its importance to the formation of the pupils, in a process that the professor is considered the key part to be dissuaded